New insight on ammonia 1.5 µm overtone spectra from two-temperature analysis in supersonic jet. (April 2019) - Svoboda, Vít; Rakovský, Jozef; Votava, Ondrej
Highlights: New high-resolution spectroscopic data for the 1.5 mm region of ammonia in the slit-jet supersonic expansion. Spectra recorded at 20 ∼ K and 80 ∼ K, respectively. Two-temperature analysis based on line intensity variation using those jet spectra was presented. Reliable determination of low-J″ rotational assignments. Empirical rotational assignments were performed for 46 ro-vibrational transitions between 6500 cm − 1 and 6900 cm − 1, respectively. Altogether, band origins for 7 vibrations have been determined, two of them for the first time. Abstract: The paper presents new high-resolution spectroscopic data for the 1.5 µm region of ammonia. All measurements have been taken in the slit-jet supersonic expansion leading to effective rotational cooling and thus facilitating significant simplification of the spectra. We demonstrate the method of controlling the expansion temperature by changing the ammonia concentration and total stagnation pressure in the jet. This allows recording spectra at 20 K and 80 K, respectively. We demonstrate two-temperature technique based on line intensity analysis using those jet spectra, that proves very effective in determining the lower state energies for states with J ″ = 0, 1, and 2 . The transitions originating from such states are especially important for the identification of vibrational band origins and a critical evaluation of the accuracy of the latest theoretical calculations. Empirical rotational assignments were performed for 46 ro-vibrational transitions between 6500 cm − 1 and 6900 cm − 1, respectively. Seven lines have been identified as R (0) transitions with J ″ = K ″ = 0, four of which are first-time identifications and/or corrections of previous misassignments. The assignments were then reconfirmed using the R (0) - P (2) ground state combination differences. Additional corresponding P (1) transitions terminating in the J ′ = K ′ = 0 upper level were found. These point straight to the vibrational band origins. Altogether, band origins for 7 vibrations have been determined and the corresponding R (0), P (1) and P (2) lines have been assigned. Finally, the experimental data are compared to highly-accurate theoretical predictions for ammonia in this spectral range.